Basic Listening Skills in English Language Learning: Foundations and Pedagogical Approaches - Nur Istiqamah (Yayasan pendidikan dzurriyatul Quran, 2023)
Listening is a fundamental skill in English as a Foreign Language (EFL) learning, providing the foundation for developing speaking, reading, and writing. This study aims to explore the foundations of basic listening skills and examine pedagogical approaches that can effectively foster listening competence. Using a qualitative descriptive design, data were obtained from literature analysis, classroom observation, and teacher interviews, then analyzed thematically to identify key challenges and strategies. Findings show that listening skills play a vital role in vocabulary development, grammatical awareness, and intercultural competence, yet learners face barriers such as fast speech rates, accent variation, and limited strategy use. Innovative approaches such as extensive listening, podcast integration, task-based learning, and mobile-assisted instruction emerge as effective solutions for enhancing learner autonomy and communicative fluency. The study implies that listening pedagogy should move beyond comprehension testing toward equipping learners with strategic, cultural, and technological resources to meet global communication demands.